2011
DOI: 10.3390/membranes1030162
|View full text |Cite
|
Sign up to set email alerts
|

Thinking in Terms of Structure-Activity-Relationships (T-SAR): A Tool to Better Understand Nanofiltration Membranes

Abstract: A frontier to be conquered in the field of membrane technology is related to the very limited scientific base for the rational and task-specific design of membranes. This is especially true for nanofiltration membranes with properties that are based on several solute-membrane interaction mechanisms. “Thinking in terms of Structure-Activity-Relationships” (T-SAR) is a methodology which applies a systematic analysis of a chemical entity based on its structural formula. However, the analysis become more complex w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…The virgin membrane surface appeared 14 homogenous, while after four weeks of exposure to sulphuric acid, the emergence of scattered areas with 15 changes in the selective layer and an increase in RMS roughness was noticed from 3.4 ± 0.2 nm to 1.9 ± 0.2 nm, 16 indicating degradation of the selective layer and exposing the support layer. The small value of roughness was 17 also reported by Fernández et al [41], who concluded that the roughness of NF270 in comparison with a fully 18 aromatic NF membrane NF90 was overtly lower as a consequence of the cross-linking degree of the monolayers 19 that constitutes the membrane surface. the fact that the radiation penetration depth was higher than the thickness of the active layer.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…The virgin membrane surface appeared 14 homogenous, while after four weeks of exposure to sulphuric acid, the emergence of scattered areas with 15 changes in the selective layer and an increase in RMS roughness was noticed from 3.4 ± 0.2 nm to 1.9 ± 0.2 nm, 16 indicating degradation of the selective layer and exposing the support layer. The small value of roughness was 17 also reported by Fernández et al [41], who concluded that the roughness of NF270 in comparison with a fully 18 aromatic NF membrane NF90 was overtly lower as a consequence of the cross-linking degree of the monolayers 19 that constitutes the membrane surface. the fact that the radiation penetration depth was higher than the thickness of the active layer.…”
supporting
confidence: 60%
“…novelties of this work are, on the one hand, the efforts to describe the ion transport mechanisms through the NF 40 membrane considering ion speciation and, on the other, the effect of ageing the membrane on its performance in 41 filtering the synthetic AMD. 42 Membranes, reagents and solutions 2 Experiments were carried out with samples of commercial NF270 membrane supplied by Dow Chemical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diante dos resultados obtidos através das duas técnicas foi possível observar a relação entre a rugosidade e hidrofobicidade das membranas. Apesar das membranas serem de poliamida, a maior hidrofobicidade da NF90 apresentada pelas medidas do ângulo de contato pode estar relacionada a sua rugosidade, além desta ser totalmente aromática (Fernández et al, 2011). Já a membrana de osmose inversa apresentou menor rugosidade e hidrofobicidade.…”
Section: Equipamento E Membranasunclassified
“…The hydrated ionic radius of the Ca 2+ ions are much larger than nitrate NO 3 ions and hence its easy passage through the membrane will be restricted however, since the PA rejection layer is negatively charged, it would also promote sorption of Ca 2+ ions on its membrane interface which could eventually lead to permeation of some of the Ca 2+ ions through the membrane. The PA active layer of the TFC membranes is usually negatively charged due to the presence of carboxylic functional groups [34,35] that could form complexes particularly with the divalent ions such as Ca 2+ and Mg 2+ This high reverse diffusion of CAN is evident from the results presented in Figure 6 using TW as FS (more discussion on Figure 6 is included later part of this section) although the mechanism involved in this particular case is the solution diffusion model due to the absence of ions in the FS. This reverse permeation or diffusion of Ca 2+ ions towards the FS could therefore result in the formation of CaSO 4 or gypsum scales by combining with SO 4…”
Section: Performance Of Hffo Membrane Module Under Different Draw Solmentioning
confidence: 99%